2014
DOI: 10.1371/journal.pone.0107405
|View full text |Cite
|
Sign up to set email alerts
|

Bazhen Decoction Protects against Acetaminophen Induced Acute Liver Injury by Inhibiting Oxidative Stress, Inflammation and Apoptosis in Mice

Abstract: Bazhen decoction is a widely used traditional Chinese medicinal decoction, but the scientific validation of its therapeutic potential is lacking. The objective of this study was to investigate corresponding anti-oxidative, anti-inflammatory and anti-apoptosis activities of Bazhen decoction, using acetaminophen-treated mice as a model system. A total of 48 mice were divided into four groups. Group I, negative control, treated with vehicle only. Group II, fed with 500 mg/kg/day Bazhen decoction for 10 continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 42 publications
4
42
0
Order By: Relevance
“…Bcl-2 protein can also promote the synthesis of GSH and inhibit the consumption of mitochondria GSH, to play an antioxidant role, in order to maintain mitochondrial redox homeostasis. It is also found that the lower expression level of Bcl-2 means the higher level of lipid peroxidation (30). Caspase-3 is an important executive molecule in the process of apoptosis (9).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Bcl-2 protein can also promote the synthesis of GSH and inhibit the consumption of mitochondria GSH, to play an antioxidant role, in order to maintain mitochondrial redox homeostasis. It is also found that the lower expression level of Bcl-2 means the higher level of lipid peroxidation (30). Caspase-3 is an important executive molecule in the process of apoptosis (9).…”
Section: Discussionmentioning
confidence: 98%
“…Bax/Bcl-2 ratio can also reflect the degree of apoptosis to some extent (30). Bcl-2 protein can also promote the synthesis of GSH and inhibit the consumption of mitochondria GSH, to play an antioxidant role, in order to maintain mitochondrial redox homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, JNK-null mice or iNOSnull mice were resistant to alcohol-or HFD-induced insulin resistance and apoptosis. Specific deletion or suppression of JNK1 or iNOS, with either using a specific siRNA or an inhibitor, or in knockout mouse strain, can also lead to resistance to HFD-induced insulin resistance and hepatocytes death or drug-induced liver injury (DILI) (Charbonneau & Marette, 2010;Fujimoto et al, 2005;He et al, 2015;Kamanaka et al, 2003;Saberi et al, 2014;Seki et al, 2012;Singh et al, 2009;Song, Fu, Xia, Su, & Song, 2014;Tipoe et al, 2006;. The opposite case with overexpression of these pro-oxidant proteins would increase the tissue sensitivity toward apoptotic death.…”
Section: Pathological Mechanisms Of Liver Diseasesmentioning
confidence: 99%
“…These may include the prevention of the pathways involved in oxidative stress, inflammation, apoptosis and gastric acid production 43,44 . Whole body exposing to acute doses of gamma irradiation either (6 Gy), were found to exert an oxidative stress due to generation of ROS, which characterised by elevation in TBARS and nitrite contents and depletion in reduced glutathione, as well as elevation in MPO activity and enhancing the production of cytokines such as TNF-α 45 , an effect which could have been due to ROS-mediated activation of the transcription factor Nf-κB [46][47] . Pretreatment of NS seed extract and TQ protect the tissues from oxidative stress induced by irradiation through protection against elevation in TBARS.…”
Section: Radioprotective Natural Productmentioning
confidence: 99%